2007
DOI: 10.1007/bf03194673
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of bovine leukocyte adhesion deficiency (BLAD) carriers in Indian cattle and buffalo breeds

Abstract: BLAD is an autosomal recessive genetic disease that affects Holstein-Friesian (HF) cattle worldwide. It is a disease characterized by a reduced expression of the adhesion molecules on neutrophils. The disease is caused by a mutation that replaces adenine at 383 with guanine, which causes an amino acid change from aspartic acid to glycine. Blood samples and a few semen samples were collected from 1250 phenotypically normal individuals, including HF (N=377), HF crossbred (N=334), Jersey (105), other breeds of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 6 publications
2
15
1
3
Order By: Relevance
“…However, it was considerably different from the frequency found in bulls by Patel et al (2007) in Indian Holstein Friesian crossbred cattle (2.99%), Norouzy et al (2005) in Iranian Holsteins (3.3%), Powell et al (1996) in American Holsteins (8.2%), Czarnik et al (2007) in the Polish Holstein-Friesian, Polish Red, and Polish Red-and-White breeds (4.3%), and Meydan et al (2010) in Holstein cows in Turkey (4.0%). The allele frequencies estimated for bulls may not fully reflect the allele frequencies for the breed since the tested bulls were derived from the Girolando progeny test and are therefore unlikely to represent a random sample of the population because they were included in the progeny test for their genetic superiority based on parent-average predictions.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, it was considerably different from the frequency found in bulls by Patel et al (2007) in Indian Holstein Friesian crossbred cattle (2.99%), Norouzy et al (2005) in Iranian Holsteins (3.3%), Powell et al (1996) in American Holsteins (8.2%), Czarnik et al (2007) in the Polish Holstein-Friesian, Polish Red, and Polish Red-and-White breeds (4.3%), and Meydan et al (2010) in Holstein cows in Turkey (4.0%). The allele frequencies estimated for bulls may not fully reflect the allele frequencies for the breed since the tested bulls were derived from the Girolando progeny test and are therefore unlikely to represent a random sample of the population because they were included in the progeny test for their genetic superiority based on parent-average predictions.…”
Section: Discussioncontrasting
confidence: 60%
“…The observed frequency of BLAD carriers among cows (0.76%) may be explained by the fact that this mutation is common in Holstein bulls in different countries (Norouzy et al, 2005;Akyüz and Ertuğrul, 2006;Czarnik et al, 2007;Patel et al, 2007), and carrier bulls were most likely used as founding sires during the establishment of the breed. Three of the 5 affected cows were daughters of the carrier bull evaluated in the study.…”
Section: Discussionmentioning
confidence: 99%
“…At 0.6% the frequency of FXI-deficiency carriers in the Holstein-Friesian population observed in our study is half that of the 1.2% reported in the Holstein sire population of the USA (Marron et al, 2004). The mutant gene for factor XI deficiency in Indian Holstein-Friesian cattle was higher than citrullinaemia (Murleedharan et al, 1999;Patel et al, 2006) and very much lower than BLAD (Patel et al, 2007), other autosomal recessive genetic diseases observed in Indian Holstein population. Because of the paucity of literature regarding the molecular diagnosis of FXI-deficiency, it is difficult to compare the carrierfrequency in the Indian Holstein-Friesian population to that found in other countries.…”
mentioning
confidence: 37%
“…Sığırlarda önemli verim kayıplarına neden olan otozomal çekinik kalıtsal hastalıklar çoğunlukla ırka özgüdür (6,7,8). Hem siyah-beyaz alaca hem de kırmızı-beyaz alaca holştaynlarda görülen üridin monofosfat senteaz eksikliği (DUMPS), bu tür kalıtsal bozukluklardan birisidir (8).…”
unclassified
“…Hem siyah-beyaz alaca hem de kırmızı-beyaz alaca holştaynlarda görülen üridin monofosfat senteaz eksikliği (DUMPS), bu tür kalıtsal bozukluklardan birisidir (8). Pirimidin nükleotid sentezinin son aşamasında ortaya çıkan orotik asit, üridin monofosfat senteaz enzimi (UMPS) tarafından üridin monofosfata (UMP) dönüştürülür (4,9).…”
unclassified